Poaceae communities in the savannas of the Amazon Estuary in Brazil - Antônio Elielson Sousa Rocha; Izildinha Souza Miranda (Acta Botânica Brasílica, 2014)
We sought to identify the major environmental factors that affect the diversity and distribution of Poaceae in the savannas of the Amazon Estuary. The study was conducted across seven areas of savanna in the Amazon Estuary, within which 160 subplots of 1 m² each were established within four 10 × 100 m plots. Soil samples were collected at a depth of 0-20 cm. A total of 24 Poaceae species were recorded. Only two were common to all of the areas studied (Axonopus aureus P. Beauv. and Anthaenantia lanata (Kunth) Benth). The edaphic factors that most influenced the Poaceae in the savannas studied were organic matter, coarse sand, and silt contents. Conversely, rainfall had no effect. The floristic and structural characteristics of the savannas studied suggest that Poaceae communities exhibit low diversity and a peculiar distribution pattern in which a group of species predominate in a given stretch, creating a homogeneous physiognomy. Our findings suggest that the structure of these communities is related to a gradient of soil texture, the percentage of Axonopus and Trachypogon coverage increasing and decreasing, respectively, along that gradient. These data can contribute to the understanding of plant-soil interactions in this environment, promoting strategies for conservation, management, and revegetation.